Cerebral Small Vessel Disease and Enlarged Perivascular Spaces-Data From Memory Clinic and Population-Based Settings - Gyanwali, Bibek; Vrooman, Henri; Venketasubramanian, Narayanaswamy; Wong, Tien Yin; Cheng, Ching-Yu; Chen, Christopher; Hilal, Saima (Frontiers in Neurology, 2019)
Background: Enlarged perivascular spaces (ePVS) are common finding on magnetic resonance imaging (MRI) in elderly. ePVS are thought to be associated with cerebral small vessel disease (SVD) such as white matter hyperintensities (WMH), lacunes, and cerebral microbleeds (CMBs). However, the different location of SVD and its relationship to ePVS distribution requires further investigation. Objective: To study the association between location and severity of SVD with ePVS from memory clinic and population-based settings. Methods: This study includes patients from an ongoing memory clinic based case-control study and participants from the population-based: Epidemiology of Dementia in Singapore study (EDIS). All participants underwent a comprehensive standardized evaluation including physical, medical and neuropsychological assessment and a brain MRI. CMBs and lacune location were categorised into strictly lobar, strictly deep and mixed, and ePVS location into centrum semiovale and basal ganglia. WMH volume was automatically segmented and were classified into anterior and posterior distribution. Negative binomial regression models were constructed to analyse associations between SVD and ePVS and the rate ratios (RR) and 95% confidence intervals (CI) were reported. Results: Of 375 patients (median age=73 years) from memory clinic and 583 participants (median age=70 years) from EDIS, the median total ePVS count was 17.0 and 7.0 respectively. Increased severity of SVD was not associated with total ePVS counts in both memory clinic and EDIS study. Analysis with the location of SVD and ePVS also showed similar results. However, in EDIS study, presence of ≥2 lacunes [RR=1.61, 95% CI=1.3, 2.30, p=0.009], presence of ≥2 CMBs [RR=1.40, 95% CI=1.08, 1.83, p=0.012] and higher volume of WMH [RR=1.41, 95% CI=1.10, 1.81, p=0.006] were associated with basal ganglia ePVS independent of age, gender and vascular risk factors. Conclusion: In this study, we found that the ePVS were not associated with the location and severity of SVD in the memory-clinic patients. However, only severity of SVD was associated with basal ganglia ePVS in the population-based setting. Our findings will need to be studied further in different cohorts so as to understand the mechanism underlying different SVD types in subclinical and clinical phases as well as for predicting cognitive decline.